Impulsive Response of Cantilever Beams - Saeed, Azfar (My University, 1966)
This thesis describes the analytical and experimental study of cantilever beams subjected to impulse at their tips. Tests were conducted on four beam specimens. These tests were carried out for the purpose of investigating the validity of the theory as presented in this thesis.
Title: Impulsive Response of Cantilever Beams, Author: Azfar Saeed, Location: Thode